Profile of Male Breast Cancer in Makkah Region of Saudi Arabia: A 4-Year Retrospective Analysis of Radiology and Histopathology - Muhammad Saeed; Bothaina Mohammed Abdulshakour; Najwa Abdalkabeer A. Bantan; Afnan Hisham Falemban; Munir Abdulla; Ehab M. Melibary; Ahmad H. Mufti; Mohiuddin M. Taher (International Journal of Breast Cancer)
Background. Mammography is a method widely used for the diagnosis of breast disorders in women and may help detect breast cancer in its early stages. Male breast cancer often remains undiagnosed or is poorly controlled until serious complications arise; therefore, the use of screening methods is needed to help with early diagnosis. Methods. From a total of 1,667 registered mammography cases screened, 17 male breast disease cases were included in this study. Mammography and ultrasound data were analyzed by Statistical Package of Social Sciences v.22 (SPSS). Diagnosis was made following biopsy in suspicious cases, and histopathological and immunological findings of all such patients were obtained for final diagnosis. Results. The mean age of the patients was 35 years (range, 14-70 years); 17.6% of the cases were aged 37 yrs, and 2 cases were aged 51 and 52 yrs. Of the 17 cases, 11 had breast lesions, and skin thickening was observed in only 1 case. The different patterns of lesions detected were asymmetry of the parenchyma, mastitis, and hamartoma (n=1 each), malignant lesions (n=2), and gynecomastia (n=6). According to the BI-RADS categorization, 8 cases were benign, one case was probably benign, and 2 cases were likely malignant. In the 2 cases with malignant lesions, pathological diagnosis was made after hematoxylin and eosin and immunocytochemistry examination as invasive ductal carcinoma (IDC) of no special type (NST), grade II and grade III. Conclusions. Most breast lesions in this study population were benign, while IDC was the most common malignancy encountered. Mammography is currently the most accurate and cost-effective method for detecting breast lesions. The findings of our study may help increase awareness of male breast cancer and encourage Saudi men at risk to perform self-breast exam and undergo routine breast screening.